Developing teachers’ creative writing skills to support the school literacy program - Iswatiningsih, Daroe; Pangesti, Fida; Sudiran, S. (Universitas Muhammadiyah Malang, 2020)
The problem faced by SDN Girimoyo 02 in implementing the school literacy movement was the lack of the number and type of reading material. This problem was overcome through the empowerment of teaching writing skills. Therefore, the aim of this community service was to provide creative writing assistance for SDN Girimoyo 2 teachers so that teachers can contribute reading material to fill the existing gaps. The service method was carried out through workshops and collective and personal mentoring, face-to-face and online. The results of the activity show that the teacher's main problem was exploring ideas or topics to be written about and starting to write. There were doubts and distrust of the teacher when writing, afraid that the idea is not good, not quite right, and not good. Likewise, when starting to write, the first sentence of the writing is felt to be insufficient. For this reason, the handling was carried out on the teacher by strengthening self-confidence, practicing simple writing that starts from experience to develop in writing accompanied by arguments or rationality, and writing assistance. Through this activity, teachers feel very helpful and motivated to optimize the implementation of GLS in schools. Teachers have been able to access various information related to cultural literacy and produce a joint workbook.